(untitled) (International Conference on Modern Science and Scientific Studies, 2025)
Systemic sclerosis (SSc) is a chronic autoimmune connective tissue disorder characterized by progressive fibrosis, vascular abnormalities, and immune dysregulation. Endothelial dysfunction and impaired vascular remodeling are central to its pathogenesis. Angiogenesis, regulated by proangiogenic and antiangiogenic factors, plays a critical role in tissue repair and vascular homeostasis. Platelet-derived growth factor (PDGF) promotes vascular proliferation, while thrombospondin-1 (TSP-1) is a potent angiostatic factor. Understanding the balance between these factors can provide insights into vascular pathology in SSc.